A kind of cementing heat conductive material and preparation method thereof
Through the preparation of surface modified graphite of nanosilicon, graphene and silane coupling agent, the problem of low thermal conductivity of traditional cementing materials is solved, and cementing thermal conductivity materials with high thermal conductivity and good cementing strength is achieved, which improves geothermal heat Heat exchange efficiency of wells.
Patent Information
- Application Number
- CN202310695130.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-06-12
AI Technical Summary
The thermal conductivity of traditional cementing materials is low, resulting in low heat transfer efficiency of geothermal wells, and poor cementing materials may become thermal obstacles to the underground heat transfer system.
The cementing thermal conductivity material is prepared by surface-modified graphite compounding of nanosilicon, graphene and silane coupling agent. By adjusting the mass ratio of the material and the preparation process, the thermal conductivity of the material and the cementitious strength with cement are improved.
The thermal conductivity coefficient of cementing thermal conductivity materials is significantly improved, the compatibility and cement strength with cement is improved, and the stable flowability of cement slurry and efficient heat exchange performance are ensured.
Smart Images

Figure BDA0004282953130000071 
Figure BDA0004282953130000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of well cementing, and in particular to a well cementing heat conductive material and a preparation method thereof. Background Art
[0002] As a renewable and clean energy, geothermal energy has the advantages of wide distribution, low cost, multiple uses and direct utilization. It is currently attracting much attention in the field of building heating. As the most critical link in the heat extraction system, the quality of geothermal well completion is related to how to efficiently utilize geothermal resources. Cementing is an important link in the drilling process, that is, injecting cement materials into the geothermal well casing and the annular space of the borehole wall. On the one hand, it is used to protect and support the casing in the well; on the other hand, it is used to enhance the heat exchange between the geothermal well heat exchanger and the rock and soil, while preventing cross-contamination of the underground aquifer. Therefore, for geothermal wells, how to correctly select cementing materials to improve the thermal conductivity of cementing cement is crucial to enhancing underground heat exchange. Existing studies have shown that the traditional cementing material, namely cementing cement, has a low thermal conductivity, resulting in low heat exchange efficiency in actual operation. Poor cementing materials even become thermal barriers to underground heat exchange systems. How to improve its thermal conductivity has become the core issue of cementing thermal conductive materials. Summary of the invention
[0003] In view of this, the present invention aims to provide a cementing thermal conductive material and a preparation method thereof. The cementing thermal conductive material provided by the present invention has a high thermal conductivity and excellent thermal conductivity.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a thermal conductive material for cementing, comprising nano silicon, graphene and graphite surface-modified by a silane coupling agent; the mass ratio of the graphite surface-modified by a silane coupling agent, the nano silicon and the graphene is (1-180): (1-80): (1-16).
[0006] Preferably, the mass ratio of the silane coupling agent surface-modified graphite, nano-silicon and graphene is (4-6):3:1.
[0007] Preferably, the method for preparing the surface-modified graphite by a silane coupling agent comprises the following steps:
[0008] dissolving a silane coupling agent in water to obtain a silane coupling agent solution;
[0009] The graphite and the silane coupling agent solution are mixed for modification, and the silane coupling agent surface-modified graphite is obtained after drying.
[0010] Preferably, the silane coupling agent includes one or more of vinyl silane, methacryloxysilane, 3-triethoxysilyl-1-propylamine, vinyl triethoxysilane, butadienyl triethoxysilane and 3-(2,3-epoxypropoxy)propyl trimethoxysilane; and the mass concentration of the silane coupling agent solution is 0.5 to 2.5%.
[0011] Preferably, the graphite includes one or more of natural flake graphite, earthy graphite and artificial graphite, and the particle size of the graphite is 1 to 90 μm.
[0012] Preferably, the mass of the silane coupling agent is 0.02-5% of the mass of the graphite.
[0013] Preferably, the modification temperature is 25 to 60° C. and the modification time is 12 to 24 hours.
[0014] Preferably, the nano-silicon comprises silicon dioxide and / or crystalline silicon, and the particle size of the nano-silicon is 1 to 20 nm.
[0015] Preferably, the graphene includes one or more of single-layer graphene, double-layer graphene and few-layer graphene.
[0016] The present invention provides a method for preparing the thermally conductive cementing material described in the above technical solution, comprising the following steps:
[0017] The nano silicon, graphene and graphite surface modified by a silane coupling agent are mixed to obtain a well cementing thermal conductive material.
[0018] The present invention provides a cementing thermal conductive material, comprising nano silicon, graphene and graphite modified by a silane coupling agent; the mass ratio of the graphite modified by a silane coupling agent, nano silicon and graphene is (1-180): (1-80): (1-16). In the present invention, the graphite modified by a silane coupling agent has a low surface energy and is easily infiltrated by cement macromolecules, thereby increasing the dispersion and adhesion of the thermal conductive material, improving its fluidity with cement and increasing the thermal conductivity of the thermal conductive material; the nano silicon particles can be adsorbed on the surface of graphene and graphite, providing a solid skeleton support and strong mechanical stress, thereby increasing the bonding strength with cement and the stability of the thermal conductive material. The present invention uses the nano silicon, graphene and silane coupling agent surface modified graphite to form a thermal conductive material with high thermal conductivity. Moreover, the thermal conductive material can be evenly dispersed in cement slurry and has good compatibility with cement and cement slurry additives, ensuring the stable fluidity of the thermal conductive cement slurry. In addition, the thermal conductive material has good bonding with cement, can improve the bonding quality of the cement ring, and increase the strength of cement stone.
[0019] The results of the embodiments show that when the thermal conductive cementing material provided by the present invention is added to cement, the thermal conductivity is 1.891-2.011 W / m·k; the rheological properties of the cement slurry do not change much, and the fluidity is very good; the average cement ring I interface bonding strength is 3.01-3.45 MPa, and the average cement ring II interface bonding strength is 1.29-1.43 MPa. DETAILED DESCRIPTION
[0020] The invention provides a thermal conductive material for cementing, comprising nano silicon, graphene and graphite surface-modified by a silane coupling agent; the mass ratio of the graphite surface-modified by a silane coupling agent, the nano silicon and the graphene is (1-180): (1-80): (1-16).
[0021] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known to those skilled in the art.
[0022] The well cementing thermal conductive material provided by the present invention comprises graphite surface-modified by a silane coupling agent. In the present invention, the preparation method of the graphite surface-modified by a silane coupling agent preferably comprises the following steps:
[0023] dissolving a silane coupling agent in water to obtain a silane coupling agent solution;
[0024] The graphite and the silane coupling agent solution are mixed for modification, and the silane coupling agent surface-modified graphite is obtained after drying.
[0025] In the present invention, the silane coupling agent preferably includes one or more of vinyl silane, methacryloxysilane, 3-triethoxysilyl-1-propylamine, vinyl triethoxysilane, butadienyl triethoxysilane and 3-(2,3-epoxypropoxy)propyl trimethoxysilane, more preferably a mixture of vinyl silane and 3-triethoxysilyl-1-propylamine, and the mass ratio of vinyl silane and 3-triethoxysilyl-1-propylamine in the mixture is preferably 3:2. In the present invention, the mass concentration of the silane coupling agent solution is preferably 0.5-2.5%, more preferably 0.5-1%. In the present invention, the graphite preferably includes one or more of natural flake graphite, earthy graphite and artificial graphite, and the particle size of the graphite is preferably 1-90 μm. In the present invention, the graphite is preferably added in the form of a graphite dispersion, and the graphene dispersion is preferably obtained by ultrasonically dispersing graphite in water, and the graphite is preferably washed multiple times with ethanol and deionized water before ultrasonic dispersion. In the present invention, the mass of the silane coupling agent is preferably 0.02-5% of the mass of the graphite, and more preferably 3.5-4.5%. In the present invention, the temperature of the modification is preferably 25-60°C, the time is preferably 12-24h, and the modification is preferably carried out under stirring; after the modification, the obtained modified liquid is preferably cooled to room temperature and then filtered, and the solid phase product is dried to obtain silane coupling agent surface modified graphite; the drying temperature is preferably 70-118°C, and the time is preferably 15min-24h, and the specific drying time is subject to constant weight.
[0026] In the present invention, the graphite has a lower surface energy after being surface-modified by a silane coupling agent and is easily wetted by cement macromolecules, thereby improving the dispersion and adhesion of the thermal conductive material, improving its fluidity with cement and increasing its bonding strength with cement.
[0027] The cementing thermal conductive material provided by the present invention includes nano silicon; the nano silicon preferably includes silicon dioxide and / or crystalline silicon, and the particle size of the nano silicon is preferably 1 to 20 nm. In the present invention, the nano silicon particles can be adsorbed on the surface of graphene and graphite, thereby improving the bonding strength of cement and the stability of the thermal conductive material.
[0028] The well cementing thermal conductive material provided by the present invention includes graphene; the graphene preferably includes one or more of single-layer graphene, double-layer graphene and few-layer graphene. In the present invention, the graphene has fast electron movement speed, strong electrical conductivity, ultra-high strength, and good toughness, which significantly helps the thermal conductivity and comprehensive performance of the entire thermal conductive material.
[0029] In the present invention, the mass ratio of the silane coupling agent surface modified graphite, nano silicon and graphene is (1-180): (1-80): (1-16), preferably (1-50): (1-10): (1-5), and more preferably (4-6): 3: 1. In the present invention, the silane coupling agent surface modified graphite and graphene are compounded with nano silicon in a certain ratio to form a thermal conductive material, which is added to cement for use, which can effectively improve the thermal conductivity of the cementing material.
[0030] The present invention provides a method for preparing the thermally conductive cementing material described in the above technical solution, comprising the following steps:
[0031] The nano silicon, graphene and graphite surface modified by a silane coupling agent are mixed to obtain a well cementing thermal conductive material.
[0032] In the present invention, the mixing is preferably stirring mixing. The present invention has no special requirements on stirring conditions, as long as the components are mixed evenly.
[0033] The well cementing thermal conductive material and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0034] Example 1
[0035] (1) adding water to 2.5 g of a silane coupling agent (the silane coupling agent is a mixture of vinyl silane and 3-triethoxysilyl-1-propylamine in a mass ratio of 3:2) to prepare a 0.5 wt% silane coupling agent solution;
[0036] (2) washing the surface of 60 g of graphite with ethanol and deionized water for multiple times, then adding the graphite into water for ultrasonic dispersion to obtain a stable graphite dispersion; adding 0.5% silane coupling agent solution in (1) into the graphite dispersion, stirring and reacting at 60° C. for 12 h; then cooling to room temperature and filtering and separating, placing the product obtained by filtration in a vacuum oven, and drying at 70° C. for 24 h to obtain silane coupling agent surface modified graphite;
[0037] (3) The graphite surface modified by the silane coupling agent in (2) is mixed with nano-silicon and graphene in a mass ratio of 4:3:1 to obtain a cementing thermal conductive material.
[0038] Example 2
[0039] The mass ratio of the silane coupling agent surface-modified graphite, nano-silicon and graphene in step (3) of Example 1 was adjusted to 5:3:1, and the rest was the same as Example 1 to obtain a cementing thermal conductive material.
[0040] Example 3
[0041] The mass ratio of the silane coupling agent surface-modified graphite, nano-silicon and graphene in step (3) of Example 1 was adjusted to 6:3:1, and the rest was the same as Example 1 to obtain a cementing thermal conductive material.
[0042] Comparative Example 1
[0043] The thermal conductive material was omitted as a blank control.
[0044] Comparative Example 2
[0045] Graphite without surface modification by silane coupling agent was used as thermal conductive material for comparison.
[0046] 10.8 g of the materials obtained in Examples 1 to 3 and Comparative Example 1 were weighed and added into 180 g of cement + 220 g of fresh water. The thermal conductivity of each material was evaluated. The results are shown in Table 1:
[0047] Table 1 Evaluation of thermal conductivity of cementing thermal conductive materials
[0048] formula Thermal conductivity (W / m·k) Comparative Example 1 0.258 Comparative Example 2 1.159 Example 1 1.891 Example 2 2.011 Example 3 1.910
[0049] As can be seen from Table 1, the thermal conductivity of the cement material in Comparative Example 2 with only graphite added is much better than that of the pure cement in Comparative Example 1. However, by adding the thermal conductive material obtained in Examples 1 to 3, the thermal conductivity of the cement is significantly improved, and with the increase of the surface-modified graphite with the silane coupling agent, the overall thermal conductivity is improved. When the surface-modified graphite with the silane coupling agent, nano-silicon and graphene are mixed in a mass ratio of 5:3:1, the thermal conductivity is as high as 2.011 W / m·k, which is 6.79 times higher than that in Comparative Example 1.
[0050] The cementing thermal conductive material solution prepared according to the above method was placed in a normal pressure viscosifier. After curing at room temperature for 2 hours, its rheological properties were measured using a six-speed rotary viscometer. The results are shown in Table 2, where K is the consistency coefficient and n is the fluidity index.
[0051] Table 2 Rheological parameters of cementing thermal conductive materials
[0052] formula Ф600 Ф300 Ф200 Ф100 Ф6 Ф3 n <![CDATA[K(Pa·s n )]]> Comparative Example 1 274 164 100 68 6 4 0.8014 0.5660 Comparative Example 2 301 234 189 117 16 13 0.7648 1.0143 Example 1 227 150 107 67 11 9 0.7336 0.7898 Example 2 255 170 112 72 7 6 0.7821 0.6618 Example 3 205 140 94 63 13 11 0.7005 0.7689
[0053] It can be seen from Table 2 that the fluidity of cement added with only graphite not treated with silane coupling agent becomes worse. After adding the thermal conductive material mixed with graphite treated with silane coupling agent, nano-silicon and graphene, the rheological properties of cement slurry basically change little, and the fluidity is very good, satisfying that n value is greater than 0.5 and K value is less than 0.8 Pa·s n , indicating that the thermal conductive material of cementing has good compatibility with cement.
[0054] Carry out cement paste bonding performance test indoors to evaluate the influence of cementing thermal conductive materials on the bonding quality of cement sheath. Test method of cement paste bonding strength:
[0055] (1) Before and after the cement test mold wall is scoured, cement slurry is prepared in accordance with GB / T 19139-2012 "Test Methods for Oil Well Cement" and poured into the cement test mold;
[0056] (2) placing the test mold filled with cement slurry into a cement paste curing device and curing it at 90° C. to form a cement paste bonding strength test specimen;
[0057] (3) After the curing time is reached, the cement paste bonding test sample is taken out and cooled to room temperature for testing;
[0058] (4) Place the cement-simulated casing bonding test specimen on a special fixture for bonding test, and apply stress at the cement-simulated casing interface at a loading rate of 100 N / s until the cement in the simulated casing cylinder is pressed out. Record the maximum force value loaded during the test, which is the cement-simulated casing bonding force limit F;
[0059] (5) The cement paste bonding strength C is calculated based on the tested cement paste bonding strength limit and the calculation formula of cement paste bonding strength. The calculation formula is as follows:
[0060]
[0061] In formula 1, C is the cement paste bonding strength, unit MPa; F is the cement paste bonding strength limit, unit N; S is the contact area between the cement paste and the simulated casing cylinder, unit mm 2 .
[0062] The test results of cement paste bonding strength are shown in Table 3:
[0063] Table 3 Cement sheath bonding strength data
[0064]
[0065] As can be seen from Table 3, the cement paste bonding strength is improved to a certain extent by adding only graphite; however, the cement paste bonding quality of the thermal conductive material mixed with graphite modified by silane coupling agent, nano silicon and graphite is significantly better than that of the cementing cement only with graphite added. When the graphite modified by silane coupling agent, nano silicon and graphene are mixed at a mass ratio of 5:3:1 (Example 2), the bonding strength of the interface I is increased by 74.2%, and the strength of the interface II is increased by 98.61%. This is because the thermal conductive material has a lower surface energy after being surface treated with a silane coupling agent, and is easily infiltrated by cement macromolecules, which improves the dispersion and bonding force of the thermal conductive material, improves its fluidity with cement, and improves its bonding strength with cement.
[0066] It can be seen from the above embodiments that the thermally conductive material provided by the present invention has a high thermal conductivity coefficient and has good compatibility with cement, and can improve the bonding quality of the cement sheath.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A thermally conductive material for cementing, characterized in that: It is composed of nano silicon, graphene and graphite surface modified by a silane coupling agent; the mass ratio of the graphite surface modified by a silane coupling agent, nano silicon and graphene is 5:3:1; The particle size of the nano silicon is 1 to 20 nm; The preparation method of the silane coupling agent surface-modified graphite comprises the following steps: dissolving a silane coupling agent in water to obtain a silane coupling agent solution; Mixing graphite and the silane coupling agent solution for modification, and obtaining the silane coupling agent surface-modified graphite after drying; The silane coupling agent is a mixture of vinyl silane and 3-triethoxysilyl-1-propylamine, wherein the mass ratio of vinyl silane to 3-triethoxysilyl-1-propylamine in the mixture is 3:2; and the mass concentration of the silane coupling agent solution is 0.5-2.5%.
2. The thermally conductive material for cementing according to claim 1, characterized in that: The graphite includes one or more of natural flake graphite, earthy graphite and artificial graphite, and the particle size of the graphite is 1 to 90 μm.
3. The thermally conductive material for cementing according to claim 1, characterized in that: The mass of the silane coupling agent is 0.02-5% of the mass of the graphite.
4. The thermally conductive material for cementing according to claim 1, characterized in that: The modification temperature is 25-60° C. and the modification time is 12-24 hours.
5. The thermally conductive material for cementing according to claim 1, characterized in that: The graphene includes one or more of single-layer graphene, double-layer graphene and few-layer graphene.
6. The method for preparing the thermally conductive cementing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The nano silicon, graphene and graphite surface modified by a silane coupling agent are mixed to obtain a well cementing thermal conductive material.
Citation Information
Patent Citations
Silicon dioxide / graphene / graphite compound heat-conducting silicone grease and preparation method thereof
CN105348807A
Preparation method of heat-conducting cement slurry for well cementation
CN115893913A